2017
DOI: 10.18203/2320-1770.ijrcog20170066
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Caesarean-Section rates according to Robson's ten group classification system and evaluating the indications within the groups

Abstract: Background: With Caesarean sections on the rise WHO proposes that health care facilities use the Robson's 10 group classification system to audit their C-sections rates. This classification would help understand the internal structure of the CS rates at individual health facilities identify key population groups, indications in each group and formulate strategies to reduce these rates.Methods: This was a cross sectional study for a period of 24 months at a tertiary care hospital in a tribal area of Kerala Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
5
7
0
1
Order By: Relevance
“…Ray A et al has shown that women with previous CS contributes maximum to overall CS rates followed by term primigravidas who are induced or underwent CS before labour (group 2 of original Robson's classification). 4 Similar findings were noted by Kazmi T et al, Helena et al and Tanaka et al [5][6][7] These and many other authors have highlighted on encouraging for TOLAC in order to reduce repeat sections. Attempts to reduce Repeat CS (by promoting TOLAC) for reducing overall CS rate may be under taken by full-fledged obstetric units with dedicated staff with careful selection of cases.…”
Section: 2supporting
confidence: 78%
“…Ray A et al has shown that women with previous CS contributes maximum to overall CS rates followed by term primigravidas who are induced or underwent CS before labour (group 2 of original Robson's classification). 4 Similar findings were noted by Kazmi T et al, Helena et al and Tanaka et al [5][6][7] These and many other authors have highlighted on encouraging for TOLAC in order to reduce repeat sections. Attempts to reduce Repeat CS (by promoting TOLAC) for reducing overall CS rate may be under taken by full-fledged obstetric units with dedicated staff with careful selection of cases.…”
Section: 2supporting
confidence: 78%
“…As per a study by Amita Ray et al, the CS rate for unbooked cases was 36.3% (227/624 live births) and that of booked cases was 24.3% (247/1016 live births). 12 The overall caesarean section rate in the study is 61.1% which was very high compare to other studies (Table 7). A complete analysis was done as per Robson's criteria, other studies only show certain important groups (Table 8).…”
Section: Discussionmentioning
confidence: 46%
“…This would be true for any tertiary care centre around the world. 5 During the study period our centre had the highest number of women in Robson's Group 3 followed by Groups1 and 5. Studies done in other countries spanning different time periods have shown the same trend in the both the developed and the developing world.…”
Section: Discussionmentioning
confidence: 88%
“…[1][2][3][4][5] In 1985 WHO stated that a C-section rate of above 15% is not justifiable at the same time stressed that every effort be made to provide CSection when needed rather than aim for a particular rate. 6 It is very difficult at the level of an individual health care facility, particularly tertiary care centre to determine an appropriate rate of CS.…”
Section: Introductionmentioning
confidence: 99%